Consumer Perceptions of Pattern Hair Loss: Insights from the South Korea Survey - Kim, Jino; Wan, Jovian; Sydorchuk, Olena; Yi, Kyu-Ho (Archives of plastic surgery, 2025)
Androgenic alopecia is the most common form of non-scarring hair loss, affecting both men and women with distinct regional patterns. This study aimed to investigate public perceptions, treatment behaviors, and preferences related to hair loss. A nationwide online survey was conducted from April 25 to 29, 2024, involving 2,579 participants. The questionnaire assessed sources of information, selection criteria for treatment providers, preferred treatment methods, and use of medications. Respondents most frequently relied on internet communities and social media for information. Treatment provider selection was influenced primarily by online reviews and word of mouth. Common treatments included over-the-counter products, clinic-based therapies, and oral medications. Age and gender differences significantly influenced treatment patterns and perceptions. The findings highlight the importance of digital platforms in shaping patient behavior and underscore the need for evidence-based education to guide individuals seeking treatment for hair loss.